Measles in South Africa: a community health interpretation of the data - Ferrinho, Paulo De Lyz Girou Martins (My University, 1991)
This dissertation reviews the international literature and South African literature and data on the epidemiology of Measles. The main purpose is to contribute to an understanding of the local epidemiology of the disease that will further the development of more targeted efforts for its control. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the faculty of Medicine of the University of the Witwatersrand in partial fulfillment of the requirements for the Master of Medicine (Community Health) Johannesburg, October 1991.
Keywords: Measles--epidemiology